2019
DOI: 10.1038/s41598-019-39432-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of surgical resection before palliative chemotherapy in advanced gastric cancer

Abstract: The role of palliative surgical resection in recurrent or metastatic gastric cancer is still controversial. A retrospective review was conducted on 689 patients who received palliative chemotherapy for recurrent (n = 307) or primary metastatic (n = 382) gastric cancer. Among 131 patients (89 primary metastatic and 42 recurrent) with surgical resection before chemotherpay, 75 underwent gastrectomy, 42 metastasectomy, and 14 gastrectomy with metastasectomy. The median overall survival (OS) of patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…The IRB decided to waive the informed consent for this study because it was a retrospective study using anonymized data. Studies about third or further line of chemotherapy and palliative surgical resection, which included the majority of the patients of the present study cohort, were previously reported [18,19]. However, the eligibility criteria of the current study were somewhat different from those of the previous ones with longer follow-up of patients [18,19].…”
Section: Study Populationmentioning
confidence: 85%
See 1 more Smart Citation
“…The IRB decided to waive the informed consent for this study because it was a retrospective study using anonymized data. Studies about third or further line of chemotherapy and palliative surgical resection, which included the majority of the patients of the present study cohort, were previously reported [18,19]. However, the eligibility criteria of the current study were somewhat different from those of the previous ones with longer follow-up of patients [18,19].…”
Section: Study Populationmentioning
confidence: 85%
“…Among them, 60 patients underwent complete resection of tumor lesion(s) without gross residual disease. The reasons for performing palliative surgical resection before chemotherapy were previous described [19]. All the patients with primary metastatic disease were in AJCC stage IV, except for two stage III patients with gross residual disease after resection.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Informed consent was waived by the IRB because this study was conducted using medical records of anonymized patients. Some patients (n = 9) in this study cohort were included in previous studies about palliative chemotherapy for RPMGC [4,14,15]. However, the follow-up of the patients was extended in the current study.…”
Section: Patientsmentioning
confidence: 99%
“…The survival benefit of early detection of GC in young people has come to a consensus (1,(3)(4)(5)(6)8); however, near-universal findings in young patients with GC have seen a female predominance, higher frequency of advanced lesions, and poor-differentiated tumors at presentation in comparison with older patients (1,(3)(4)(5)(6)8). Surgical resection (radical or palliative gastrectomy) is often performed for patients with potentially resectable lesions in practice, which is associated with a favorable outcome in advanced GC (13). Nevertheless, the role of survival benefits after surgical resection remains unknown in general treatment practice for advanced GC in young adults.…”
Section: Introductionmentioning
confidence: 99%